(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines theoretical and practical aspects of innovative approaches in mother tongue education. Using the 5th-grade “Zukko Kitobxon” project as an example, it analyzes how project-based tasks develop students’ communicative, linguistic, creative, and social competencies. The findings support the improvement of innovative methods and the effective organization of project activities in mother tongue teaching.